2021
DOI: 10.4240/wjgs.v13.i4.355
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis of anorectal tuberculosis by polymerase chain reaction, GeneXpert and histopathology in 1336 samples in 776 anal fistula patients

Abstract: BACKGROUND The association of tuberculosis (TB) with anal fistulas can make its treatment quite difficult. The main challenge is timely detection of TB in anal fistulas and its proper management. There is little data available on diagnosis and management of TB in anal fistulas. AIM To detect TB in fistula-in-ano patients were analyzed in different methods utilized. METHODS A retrospective analysis of different methods, polymerase chain-reacti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 22 publications
0
14
0
1
Order By: Relevance
“…It is reported that PCR was also significantly higher than histopathology in detecting TB fistulas. 33 However, using a single indicator to distinguish between the two diseases is not comprehensive. Jung et al 27 integrated seven clinical indicators and achieved 98% sensitivity and 92.4% specificity in the validation dataset for the differential diagnosis between CD and ITB.…”
Section: Discussionmentioning
confidence: 99%
“…It is reported that PCR was also significantly higher than histopathology in detecting TB fistulas. 33 However, using a single indicator to distinguish between the two diseases is not comprehensive. Jung et al 27 integrated seven clinical indicators and achieved 98% sensitivity and 92.4% specificity in the validation dataset for the differential diagnosis between CD and ITB.…”
Section: Discussionmentioning
confidence: 99%
“…In regions where Crohn’s disease is common, a colonoscopy should be done in all cases of high fistulas[ 28 ]. On the other hand, in regions where tuberculosis is common, polymerase chain-reaction (PCR) should be done in samples from the fistula (pus or fistula tract wall or tract lining)[ 24 , 29 ]. In a large series published from a TB-endemic region (India), tuberculosis was detected in 10% (133/1336) of tested samples (fistula tract lining or pus)[ 29 ].…”
Section: Challenges In Managing These Fistulasmentioning
confidence: 99%
“…The detection rate of tuberculosis was 12.5% (129/1034) by PCR, 1.5% (3/197) by histopathology, and 0.9% (1/105) by GeneXpert tests[ 29 ]. Therefore, PCR is significantly more sensitive than histopathology or GeneXpert to detect tuberculosis[ 29 ]. However, in spite of high sensitivity, it is not uncommon that tuberculosis is missed and goes undetected in the first sample.…”
Section: Challenges In Managing These Fistulasmentioning
confidence: 99%
“…2 Anti-TB treatment for extrapulmonary TB consists of a four-drugs (Isoniazid, Rifampicin, Pyrazinamide and Ethambutol) for the first 2 months (intensive phase) followed by the two-drug regimen (Isoniazid and Rifampicin) for the next 4 months (maintenance phase). 3 Pyridoxine is added to this regimen to prevent peripheral neuropathy, an adverse reaction with isoniazid.…”
mentioning
confidence: 99%